Technoeconomic Analysis of Prototype Hydropower Plant Development in Nigeria (2023)
Epileptic power supply in Nigeria has caused hindrances to her growth. Electricity is required for technological advancement and economic growth, as business transactions and most activities depend on its availability. This work was aimed at developing a prototype hydropower plant for use in riverine area(s) for electricity generation. Using Autodesk inventor software, the required turbine was designed and thereafter fabricated and assembled appropriately with all necessary components. Stress analyses (Von Mises, first, and third principal stresses) were also conducted to determine the turbine load bearing capacity. The e system was fitted into the edge of a stream (with minimum debris and cataract to prevent and reduce the blades from wear and tear) and arranged such that the blades were at an appropriate angle of attack to capture the water's kinetic energy. The turbine possessed eight blades, designed and fabricated to function in a river with low volume. On assembling the turbine with frame, gears, ball bearing and shaft, a pico-hydropower plant was developed. Stress analyses indicated Von Mises; first; and third principal stresses to respectively be: (0.00000498617; -0.00316625; and -0.0259764) MPa for minimum values and (0.0382339; 0.0452009; and 0.00873272) MPa for maximum values, indicating that the turbine can withstand operating conditions like pressure, force and friction. On testing, voltage readings were 0.90, 0.93, 0.96, 0.98 and 1.00 volts respectively. It was found to be portable and economical. The locally developed hydropower plant will be useful for solving electrification problems in rural areas, farm settlements and off-grid homes.